2013
DOI: 10.1161/circresaha.111.300539
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs as Novel Biomarkers for Platelet Activation

Abstract: Pioneering studies have revealed the presence of endogenous microRNAs (miRNAs) in the circulation that are not cell-associated. 1 The cellular origin and the biological function of circulating miRNAs, however, are less clear. Editorial, see p 576We have previously quantified circulating miRNAs in a large population-based cohort, the Bruneck study.3,4 Using concepts of network topology, 5 we identified altered miRNA signatures in patients with type 2 diabetes mellitus 3 and with future myocardial infarction. 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
362
6
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 361 publications
(392 citation statements)
references
References 15 publications
21
362
6
3
Order By: Relevance
“…The history of medication use was included in the prediction model 2 (Table 2) to investigate the effect on AMI occurrence because increasing evidence has shown that medication therapy may also alter circulating miRNA levels. 23,24 Results suggest that the medication use decreased the associations between miRNAs and AMI to a certain degree, but the associations remained significant. Of note, the miRNA levels showed no significant difference in patients with AMI with or without history of medication use before hospital admission, suggesting that the 2 miRNAs are markers of AMI rather than drug use.…”
Section: Discussionmentioning
confidence: 99%
“…The history of medication use was included in the prediction model 2 (Table 2) to investigate the effect on AMI occurrence because increasing evidence has shown that medication therapy may also alter circulating miRNA levels. 23,24 Results suggest that the medication use decreased the associations between miRNAs and AMI to a certain degree, but the associations remained significant. Of note, the miRNA levels showed no significant difference in patients with AMI with or without history of medication use before hospital admission, suggesting that the 2 miRNAs are markers of AMI rather than drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, platelet MPs are the most abundant cellderived MP subtype in the circulation [72], where relatively high levels of microRNAs originating from platelets are also found [73].…”
Section: Clinical Significance Of Platelet Mps and Micrornasmentioning
confidence: 99%
“…Circulating microRNAs have been proposed by as novel biomarkers for platelet activation [73] and coronary artery disease [77]. The group of Manuel Mayr demonstrated a substantial platelet contribution to the pool of circulating microRNAs, noting, in doing so, that the microRNA content of platelet-poor plasma differs from that of serum [73].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
See 2 more Smart Citations